Membangun Generasi Sadar Pancasila Melalui Sosialisasi dan Lomba Video Kreatif Bertema Pancasila - Trisnanto, Muhammad Rizqi Amin; Tarigan, Ari Anggriani; Amanda, Nur Aini Lila; Aiman, Laode Muhammad; Handaningrum, Riana (Jurnal Bina Desa, 2025)
The young generation is an important axis in the process of national development, this is because in this era of the fourth industrial revolution, Pancasila must be promoted through technological creativity developed by the young generation (Usiono 2024). Based on the results of observations conducted by the UNNES GIAT 9 TEAM, the Kemasan village has a youth organization in each RT. The potential of this large youth must be managed and developed properly. Through this creative video competition with the theme of Pancasila, it is hoped that it can increase insight, views, and understanding regarding the form of implementation of Pancasila values in everyday life and bring out the potential of competent youth in the field of videography. This study used the socialization and competition methods. Each youth organization was given a deadline for submitting the videos they had made on July 23, 2024, then it would be assessed according to the indicators made by the committee on July 24-25, 2024. The announcement of the winners was held at the Pendopo of the Kemasan Village Head's Office on July 26, 2024.